Primary Pyomyositis: Its Socioeconomic Effects; A Community Overview. A Qualitative Study Design - Kitara, David Lagoro; Bwangamoi, Paul Okot; Wabinga, Henry; Odida, Michael (Int J Trop Dis Health, 2015)
To assess the community’s views on the socioeconomic effects of primary pyomyositis to patients, family, health facilities and community. A cross-sectional study design using qualitative research methods. Gulu Regional and other Hospitals in Northern Uganda from September 2011 to November 2013. The study was conducted among patients with primary pyomyositis, next of kin, health workers and opinion leaders on their views on the socioeconomic effects of pyomyositis. Key Informant Interviews, Focus Group Discussions and In-depth Interviews were used to obtain qualitative information. Ethical approval for the study was obtained from Gulu University IRB and the National Council of Science and Technology (UNCS&T). Thematic content analysis was used for analysis of this qualitative data.
Keywords: Primary pyomyositis; socioeconomic effects